Asymmetric Exchange Rate Pass-Through to Consumer Prices in Ghana: Evidence from EMD-NARDL Approach. (11th August 2022) - Obeng, Camara K.; Frimpong, Siaw; Amoako, Gilbert K.; Agyei, Samuel K.; Asafo-Adjei, Emmanuel; Adam, Anokye M.
Abstract : This paper analyses the US dollar exchange rate pass-through to consumer prices in Ghana from January 1990 to January 2020 using the empirical mode decomposition-based nonlinear autoregressive distributed lags model (EMD-NARDL). This model eliminates the noise component of the underlying data and captures the short- and long-run nonlinearities. We find evidence of cointegration between denoised series of consumer prices and exchange rate and asymmetric pass-through in both the short- and long-run. Specifically, exchange rate pass-through was found to be in the long-run incomplete in the period of depreciation and statistically zero pass-through in the period of appreciation. In the short-run, the exchange rate pass-through in periods of depreciation is near complete; that is, 81% against 74% in periods of appreciation. We recommend that monetary authorities consistently monitor exchange rate behaviour and maintain efficient exchange rate management policies to ensure stable consumer prices. This could be achieved through proper and timely policy interventions using the available monetary policy tools such as foreign exchange reserves.